The Effectiveness of Artificial Intelligence in Enhancing the Journalistic Writing of Students at SMA Negeri 2 Jombang - Fallo, Said Riztieo; Masruroh, Sayidah Afyatul (Tebuireng: Journal of Islamic Studies and Society, 2026)
This study aimed to examine the effectiveness of Artificial Intelligence (AI) in improving the journalistic writing skills of students at SMAN 2 Jombang. A quantitative approach was employed using a quasi-experimental one-group pretest–posttest design. The study involved 50 students who were members of the school's journalism extracurricular organization. Participants were selected using purposive sampling. Data were collected through an analytic rubric designed to assess students' journalistic writing and were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results revealed that the mean pre-test score was 21.90, while the mean post-test score was 20.82. The hypothesis testing yielded a p-value of 0.250 (p > 0.05), indicating that there was no statistically significant difference between students' journalistic writing performance before and after the AI-assisted writing intervention. These findings suggest that, within the context of this study, AI did not demonstrate a statistically significant effect on improving the quality of students' journalistic writing. The results imply that the educational benefits of AI depend not only on access to the technology but also on longer intervention periods, structured instructional strategies, and appropriate pedagogical guidance to support the development of journalistic competence